Quantitative Analysis of Surgical Freedom and Area of Exposure in Minimal-Invasive Transcanal Approaches to the Lateral Skull Base. Issue 6 (July 2018) - Anschuetz, Lukas; Presutti, Livio; Schneider, Daniel; Yacoub, Abraam; Wimmer, Wilhelm; Beck, Juergen; Weber, Stefan; Caversaccio, Marco
Abstract : Hypothesis: We aim to provide objective data regarding the area of exposure (AOE) and the surgical freedom (SF) offered by the transcanal approaches to the lateral skull base. Background: Minimal-invasive transcanal lateral skull base procedures have been recently developed and their clinical feasibility demonstrated. The reduced access size requires careful analysis and selection of suitable cases, qualifying for a minimal-invasive approach. Methods: We performed the mentioned approaches in standardized dissection using human whole heads. Surgical freedom is defined as the degree of movement liberty of the surgical instrument at predefined landmarks. We assessed SF at anatomical landmarks throughout the lateral skull base. Moreover, we measured the AOE, defined as the surface on the lateral skull base reached by every approach. Results: We performed a total of 48 dissections under stereotactic image guidance in a total of 12 sides. The mean SF was assessed for the inferior petrous apex 602 mm 2, for the geniculate ganglion 1, 916 mm 2, and for the fundus of internal auditory canal 1, 337 mm 2 . The AOE was measured for the infracochlear approach 55 mm 2, suprageniculate approach 67 mm 2, transpromontorial approach 11 mm 2, and for the expanded transpromontorial approach 93 mm 2 at the fundus and 108 mm 2 at the porus of the internal auditory canal. Conclusion: This study provides a quantitative description of minimal-invasive transcanal approaches to the lateral skull base. The AOE offered by the expanded transcanal transpromontorial approach is inferior but comparable to the reported AOE of transmastoidal approaches. The reported objective measurements may provide important information for future preoperative planning and patient counseling.